The Impact of MSMEs Financing in Islamic Bank on Unemployment in Indonesia - Mohammad Zen Nasrudin Fajri; Azidni Rofiqo; Abdul Latif Rizqon; Raditya Hasan (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT One of the contributions of the Islamic banking sector to Indonesia's economy is channeling funds to MSMEs in the form of financing since a number of them could not access financial services. Interestingly, the MSMEs grew as the Islamic Banking sector rose. However, no single study analyzes such an impact on unemployment in both rural and urban areas. This paper aimed to reveal the effect of MSMEs financing in Islamic banks on unemployment in Indonesia. It further aimed to discover such an effect on unemployment in Indonesia's urban and rural areas separately. Dynamic panel GMM two-step analysis is used in this research to estimate cross-province data in Indonesia between 2010 and 2019. The results of the study reveal that MSMEs financing in Islamic Banks contributed significantly to the reduction of unemployment in Indonesia as a whole. It is also found that the unemployment in urban areas is reduced by MSMEs financing in Islamic Banks. On the other hand, there is no significant relationship between MSMEs financing in Islamic Banks and unemployment in rural areas. These findings can be the basis for Islamic banks to increase MSMEs financing and for the government to expand Islamic banks' role in every part of Indonesia to reduce unemployment, especially in rural areas. Keywords: MSMEs Financing, Islamic Bank, Unemployment, Urban, Rural.   ABSTRAK Salah satu kontribusi sektor perbankan syariah dalam perekonomian Indonesia adalah penyaluran dana kepada UMKM dalam bentuk pembiayaan, karena beberapa dari mereka tidak dapat mengakses layanan keuangan. Menariknya, UMKM tumbuh seiring dengan bangkitnya sektor Perbankan Syariah. Namun, tidak ada satu studi pun yang menganalisis dampak tersebut terhadap pengangguran di pedesaan dan perkotaan. Penelitian ini bertujuan untuk mengungkap pengaruh pembiayaan UMKM di bank syariah terhadap pengangguran di Indonesia. Hal ini bertujuan untuk mengetahui lebih jauh pengaruh tersebut terhadap pengangguran di daerah perkotaan dan pedesaan secara terpisah di Indonesia. Analisis dua langkah GMM panel dinamis digunakan untuk mengestimasi data lintas provinsi di Indonesia antara tahun 2010 dan 2019. Hasilnya mengungkapkan bahwa pembiayaan UMKM di Bank Syariah berkontribusi signifikan terhadap pengurangan pengangguran di Indonesia secara keseluruhan. Ditemukan juga bahwa pengangguran di perkotaan berkurang dengan pembiayaan UMKM di Bank Syariah. Di sisi lain, tidak ada hubungan yang signifikan antara pembiayaan UMKM di bank syariah dengan pengangguran di pedesaan. Hasil penelitian ini dapat menjadi dasar bagi bank-bank syariah dalam meningkatkan porsi pembiayaan UMKM dan dasar bagi pemerintah untuk memperluas peran perbankan syariah di seluruh bagian Indonesia untuk mengurangi pengangguran, khususnya di area pedesaan. Kata Kunci: Pembiayaan UMKM, Bank Syariah, Pengangguran, Perkotaan, Pedesaan.